KEPASTIAN HUKUM DALAM PROSES PERADILAN ATAS DUA LAPORAN PERBUATAN PIDANA YANG BERBEDA DALAM PERISTIWA YANG SAMA OLEH PENGADILAN - Hasibuan, Riski Wandy; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The Republic of Indonesia is a constitutional state based on Pancasila and the Constitution of 1945 by upholding moral values, ethics, character, and personality noble nation, faith, and fear of God Almighty, respecting diversity in social life, nation and the state, as well as to protect the dignity of every citizen. State law rests on keyakinanan that state power must be run on the basis of fair and good law. The purpose of the law of the state is able to create comfort and order in the society, but it is also the most substantial legal purpose is to promote justice in society and the creation of legal certainty and expediency. From the above results of the exposure, the authors are interested in discussing Rule of Law in Judicial Proceedings Top Two Different Report of Criminal Acts in the same incident by the Court.The purpose of this study was to determine the legal certainty in issues involving Yuli Rahmawati persecution and Murya Supreme Goddess and legal safeguards for citizens against state tyranny.This study is a descriptive normative research, which consists of primary data, secondary and tertiary. Data collection tools in the form of literature studies or studies document. The data have been collected and grouped be analyzed qualitatively and diseimpulkan deductively.Legal certainty in criminal court ruling that gave birth to two people convicted basically not run well as what to expect countries that have declared themselves as a state based on law. Legal certainty means a country's legal system capable of guaranteeing the rights and obligations of every citizen. And then known as crimen crimen sine lege principle, which is the goal provide legal protection for citizens against state tyranny. Because the essence of the rule of law is a matter of protection of acts of arbitrariness. To ensure legal certainty there should be codified, which is the effort to record the written regulations are still separated into a book systematically. The main purpose is to abolish laws that are outside the statute books with the aim to achieve a maximum of legal certainty in the community. And to achieve the goals of criminal procedural law is that it can find the real truth of the material.Keywords: State, Law, Legal Certainty